1998
DOI: 10.1093/clinchem/44.3.578
|View full text |Cite
|
Sign up to set email alerts
|

Bone formation and resorption biological markers in cosmonauts during and after a 180-day space flight (Euromir 95)

Abstract: Long-term spaceflights induce bone loss as a result of profound modifications of bone remodeling, the modalities of which remain unknown in humans. We measured intact parathyroid hormone (PTH) and serum calcium; for bone formation, serum concentrations of bone alkaline phosphatase (BAP), intact osteocalcin (iBGP), and type 1 procollagen propeptide (PICP); for resorption, urinary concentrations (normalized by creatinine) of procollagen C-telopeptide (CTX), free and bound deoxypyridinoline (F and B D-Pyr), and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(81 citation statements)
references
References 19 publications
3
78
0
Order By: Relevance
“…Results obtained from humans and rodents after spaceflights indicate that bone mass changes are site specific rather than evenly distributed throughout the skeleton, with the weight‐bearing bones more affected than the non‐weight‐bearing bones [Carmeliet and Bouillon, 1999]. Microgravity induces an uncoupling of bone remodeling equilibrium between bone formation and resorption, which could count for the bone loss [Caillot‐Augusseau et al, 1998]. These changes result in weakened and brittle bones prone to fracture on re‐entry and in accelerated osteoporosis, making bone deterioration a major problem obstructing the prospects of long‐duration manned spaceflight [Baldwin et al, 1996].…”
supporting
confidence: 80%
“…Results obtained from humans and rodents after spaceflights indicate that bone mass changes are site specific rather than evenly distributed throughout the skeleton, with the weight‐bearing bones more affected than the non‐weight‐bearing bones [Carmeliet and Bouillon, 1999]. Microgravity induces an uncoupling of bone remodeling equilibrium between bone formation and resorption, which could count for the bone loss [Caillot‐Augusseau et al, 1998]. These changes result in weakened and brittle bones prone to fracture on re‐entry and in accelerated osteoporosis, making bone deterioration a major problem obstructing the prospects of long‐duration manned spaceflight [Baldwin et al, 1996].…”
supporting
confidence: 80%
“…Two-way ANOVA indicates significant effects of gender (P ϭ 0.036) and hindlimb unloading (P ϭ 0.0005), with no interaction between the 2 variables. tion and increased bone resorption (1,6,15,22,38,39). However, bone histology has not been investigated in astronauts, and the changes in biochemical markers of bone metabolism have not been entirely consistent (24).…”
Section: Discussionmentioning
confidence: 99%
“…Post‐flight analysis revealed that a recovery time in normal gravity equivalent to the flight duration was insufficient to restore bone mineral density levels to the pre‐flight status (Vico et al ., ). Investigations on cosmonauts who experienced a 6‐month unloading exposure revealed that, as per 1‐month spaceflight, serum levels of ALP, osteocalcin and type I procollagen pro‐peptide were reduced (Caillot‐Augusseau et al ., ). In cosmonauts a bone mineral loss equivalent to an average of 3.5% (primarily in weight‐bearing bones) after a 16–28 weeks spaceflight was observed by means of dual energy X‐ray absorptiometry (DEXA) analysis (LeBlanc et al ., ).…”
Section: Near‐zero Gravity Studies During Spaceflightmentioning
confidence: 97%
“…However, available information indicate uncoupling of bone remodelling with enhancement of the expression of bone resorption markers, an increase in urinary collagen degradation crosslink products and a reduction in the expression of bone‐formation markers (Smith et al ., ). In agreement with an increased bone resorption, recent publications confirmed that deoxypyridinoline and the C ‐terminal peptide of type I collagen increased after a 3‐month spaceflight (Caillot‐Augusseau et al ., ; Zayzafoon et al ., ). Bone demineralization was associated with enhancement of calcium and phosphorus excretion (Zittermann et al ., ; Smith et al ., ).…”
Section: Near‐zero Gravity Studies During Spaceflightmentioning
confidence: 99%